Developing Non-Positional Teacher Leadership of Formative Assessment Practices: Findings from the Teacher-Led Learning Circles Project - Campbell, Carol; DeLuca, Christopher; LaPointe-McEwan, Danielle; Rickey, Nathan; Ceau, Maeva (International Journal of Education Policy and Leadership, 2025)
This article examines the development of teacher leadership through the Teacher-Led Learning Circles project, a professional learning and research initiative across seven countries: Brazil, Côte d’Ivoire, Ghana, Malaysia, South Korea, Switzerland, and Uruguay. Through targeted professional development over one academic year, the project advanced non-positional teacher leadership and confidence in four core formative assessment strategies as well as the embedded use of these strategies by teachers. Data were collected through multiple sources, including a teacher pre-survey (n = 171), a teacher post-survey (n = 121), a teacher codification framework questionnaire (n = 113), a local facilitator questionnaire (n = 27), a local union representative questionnaire (n = 10), a national researcher questionnaire (n = 7), and seven country profiles. Findings show that when teachers are supported, their influence grows, and formative assessment practices become more embedded and confident, highlighting the potential of teacher-led professional development for sustainable educational improvement.